Platelet‐Derived Mitochondria Display Embryonic Stem Cell Markers and Improve Pancreatic Islet β‐cell Function in Humans. (7th July 2017) - Zhao, Yong; Jiang, Zhaoshun; Delgado, Elias; Li, Heng; Zhou, Huimin; Hu, Wei; Perez‐Basterrechea, Marcos; Janostakova, Anna; Tan, Qidong; Wang, Jing; Mao, Mao; Yin, Zhaohui; et al.
Abstract: Diabetes is a major global health issue and the number of individuals with type 1 diabetes (T1D) and type 2 diabetes (T2D) increases annually across multiple populations. Research to develop a cure must overcome multiple immune dysfunctions and the shortage of pancreatic islet β cells, but these challenges have proven intractable despite intensive research effort more than the past decades. Stem Cell Educator (SCE) therapy—which uses only autologous blood immune cells that are externally exposed to cord blood stem cells adhering to the SCE device, has previously been proven safe and effective in Chinese and Spanish subjects for the improvement of T1D, T2D, and other autoimmune diseases. Here, 4‐year follow‐up studies demonstrated the long‐term safety and clinical efficacy of SCE therapy for the treatment of T1D and T2D. Mechanistic studies found that the nature of platelets was modulated in diabetic subjects after receiving SCE therapy. Platelets and their released mitochondria display immune tolerance‐associated markers that can modulate the proliferation and function of immune cells. Notably, platelets also expressed embryonic stem cell‐ and pancreatic islet β‐cell‐associated markers that are encoded by mitochondrial DNA. Using freshly‐isolated human pancreatic islets, ex vivo studies established that platelet‐releasing mitochondria can migrate to pancreatic islets and be taken up by islet β cells, leading to the proliferation and enhancement of islet β‐cell functions. These findings reveal new mechanisms underlying SCE therapy and open up new avenues to improve the treatment of diabetes in clinics. Stem Cells Translational Medicine 2017;6:1684–1697 Abstract : The feature of platelets was changed in diabetic subjects after receiving Stem Cell Educator (SCE) therapy.